Penggunaan Biosorben Biji Pepaya Untuk Merekondisi Kualitas Minyak Jelantah - Muhammad Iqbal Nusa; Yunan Bakri Sipahutar (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2018)
This research objective has to show the effectivity of the using biosorbent Papaya seed to recondition of fried oil quality.  The adsorption mechanizme and the factors effected to performance of biosorbent must studied Comprehensively. Totality of extent particle surface and the long time of biosorbent with adsorbed interface determined performance adsorption. The research was compiled to producing and activating Papaya seed as biosorbent; and then to do the experiment for effectivity biosorbent according with Complete Random Factorial Design, with two factor namely Mass biosorbent to Volume fried oil ratio (A1=5 %, A2 = 10 %, A3 = 15 %, dan A4 = 20 % (b/v) , and the long time of biosorbent fried oil interface (L1 = 2, L2 = 4, L3 = 6, dan L4 = 8 days).  The result of data analysis to show that  effect of Mass biosorbent to Volume fried oil ratio factor have significant  different  among factor level properly (p<0.05), the mean value of Peroxide Number, Free Acid Number, and Water Content of fried oil  were tendence to below.  But the value of organoleptic colour was increase.  Effect of the long time of biosorbent fried oil interface have significant  different  among factor level properly (p<0.05), the  mean value of Peroxide Number, Free Acid Number, and Water Content of fried oil  were tendence to increase, and the value of organoleptic colour were also.